Inflammasomes as Potential Therapeutic Targets in Atherosclerotic Cardiovascular Disease - Wang, Ping; Ma, Jun; Zhang, Ru (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Recent studies have shown that interleukin 1β monoclonal antibody improves the prognosis of patients with coronary artery disease independently of lipid levels, providing the first evidence of the effectiveness of anti-inflammatory treatment for atherosclerotic disease. However, there is still a significant risk of residual inflammation with interleukin 1β monoclonal antibody therapy alone. Activation of the inflammasome, an intracellular protein complex composed of pattern recognition receptors and other inflammatory molecules, is a critical step in the development of the inflammatory response, and targeting the inflammasome to reduce residual inflammation has emerged as a new idea in the anti-inflammatory treatment of atherosclerotic disease. This review discusses the role and mechanisms of inflammasomes in atherosclerotic disease and lists drugs that are currently thought to potentially treat atherosclerosis through antiinflammasomes, hoping to provide insight into the development of new anti-inflammatory therapies for the prevention and treatment of atherosclerotic disease.
Keywords: coronary artery disease